Product characteristics and the growth of FDI - Frank G. Barry; Aoife Hannan (University College Dublin, Department of Economics, 2002)
FDI and the activities of foreign affiliate firms have grown dramatically in recent decades, both in absolute terms and as a share of world GDP. Most explanations of this phenomenon focus on the impact of the macroeconomic environment on the choices facing individual firms over whether or not to engage in FDI. We focus instead on the characteristics of demand for the products produced in sectors known to be conducive to FDI. These characteristics are shown to help explain the recent growth in the FDI-to-GDP ratio.
hdl:10197/1274
Keywords: 330; Direktinvestition; Multinationales Unternehmen; Einkommenselastizität; Branche; Irland